Embodied visions evolution, emotion, culture, and film - Grodal, Torben Kragh (Oxford University Press, 2009)
Torben Grodal presents an analysis of film through the lens of bioculturalism, revealing how human biology as well as human culture determine how films are made and experienced. He uses the breakthroughs of modern brain science to explain features of film aesthetics and to construct a general model of aesthetic experience.